Association between early mobility scim measures and walking function in spinal tuberculosis - L.N. Yong; Fatimah Ahmedy; Khin, Nyein Yin; S.S. Syah; Tan, Soo Fun; Nooralisa Mohd Tuah (Faculty of Science and Natural Resources, 2020)
Spinal Tuberculosis (STB) often led to walking impairment which could lower a patient’s quality of life. This study aimed to determine the association between the early mobility Spinal Cord Independence Measure (mSCIM) and walking function beyond one year of STB diagnosis. This cross-sectional analytical study was conducted by collecting data via focused history taking, clinical assessment, and clinical notes referencing of STB patients attended the rehabilitation follow-up at Queen Elizabeth Hospital, Kota Kinabalu. A total of 36 patients were recruited and grouped as “walking” or “non-walking” based on ability to achieve a minimal level of 6 based on the Walking Index for Spinal Cord Injury (WISCI). Significant difference in mSCIM between the two groups were analysed using logical regression. The results showed that the mSCIM scores between walking and non-walking patients were significantly different (pvalue=0.021, OR=14.9, 95% CI=1.515-147.404). The results were then compared with previous literature. In conclusion, individuals with a higher mSCIM (a score of more than or equal to 13) have higher likelihood of walking beyond one year of STB diagnosis.